Effect of fabrication technique on optical properties of carbon nano-dots from gac fruit (momordica cochinchinensis spreng) skin - Lê, Xuân Diễm Ngọc; Đỗ, Thanh Tiến; Ngô, Khoa Quang (Hue University Journal of Science: Natural Science, 2025)
In this study, we fabricated carbon dots (CDs) solutions from the skin of the Gac fruit by using the hydrothermal method. The samples were fabricated at 190 °C for 6, 8, 10, 12, 14, and 16 hours. We investigated the structural properties of the obtained CDs via X-Ray diffraction (XRD), and the optical properties of the samples were accessed via UV–Vis absorption, photoluminescence, FTIR spectra, and the quantum yield. The results show that the CDs absorb light at the wavelength of 276 nm and emit at the wavelength of 430 nm. The FTIR spectrum clarifies that the functional groups on the surface of the carbon core are hydroxyl and carbonyl. The results indicate that the quantum yield varies with the treatment time and reaches a maximal value (5,06%) at 190 °C and 14 hours.